1987
DOI: 10.1017/s0022112087002684
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity and passive-scalar dynamics in two-dimensional turbulence

Abstract: The dynamics of vorticity in two-dimensional turbulence is studied by means of semi-direct numerical simulations, in parallel with passive-scalar dynamics. It is shown that a passive scalar forced and dissipated in the same conditions as vorticity, has a quite different behaviour. The passive scalar obeys the similarity theory à la Kolmogorov, while the enstrophy spectrum is much steeper, owing to a hierarchy of strong coherent vortices. The condensation of vorticity into such vortices depends critically both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 23 publications
12
88
0
Order By: Relevance
“…We have indeed found in our numerical 2D simulations that, for times longer than an initial enstrophy time scale, the two gradients have an identical orientation in most of the domain. This is also confirmed by Babiano et al [1] who have noted that isolines of tracer and vorticity have similar orientations. Therefore, the present results are valid for both gradients.…”
Section: Resultssupporting
confidence: 82%
“…We have indeed found in our numerical 2D simulations that, for times longer than an initial enstrophy time scale, the two gradients have an identical orientation in most of the domain. This is also confirmed by Babiano et al [1] who have noted that isolines of tracer and vorticity have similar orientations. Therefore, the present results are valid for both gradients.…”
Section: Resultssupporting
confidence: 82%
“…The degree of correlation in two-dimensional turbulence between passive scalars and vorticity does not appear to be the subject of consensus. Babiano et al (1987) claim there is no correlation. However the simulations of Holloway & Kristmannsson (1984) and Holloway, Riser & Ramsden (1986) suggest that tracer is being concentrated in vortex cores and strained between the cores.…”
Section: Hydrodynamics Of Forced Vortex Flowsmentioning
confidence: 93%
“…In decaying 2D turbulence, it has been shown that at sufficiently large times, when the coherent structures are well-formed, some aspects of the system evolution may be modelled in terms of a limited number of interacting point vortices [3,5]. In forced turbulence, the turbulent field among the coherent structures is not as passive as in decaying flows; new coherent structures are continuously formed in the background field and a statistically stationary state may be obtained [4,6].…”
Section: Introductionmentioning
confidence: 99%